Răspunsuri

2014-11-15T00:33:07+02:00
2014-11-15T00:53:22+02:00
A)(27-4)(3√3+4)=3√81+4√27-12√3-16
                        =3x9+4x3√3-12√3-16
                        =27+12√3-12√3-16
                        =11
b)(√2+1)²+2√8=2+2√2+1+2x2√2
                    =3+2√2+4√2
                    =2+6√2
c)(√5-2)²+4(√5-1)=5-4√5+4+4√5-4
                        =5  (se reduc termenii:-4√5 cu +4√5 si +4 cu -4)

La b) si c) parantezele la patrat sa calculeaza dupa formule de calcul prescurtat astfel:
(a+b)²=a²+2ab+b²
(a-b)²=a²-2ab+b²

1 5 1